Football as A Character Formation Medium 7 Habits of Great Indonesian Children in One of The Elementary Schools in Labuhan Ratu District - Putra, Yuda Gastriana; Lengkana, Anggi Setia; Susilawati, Dewi (Universitas Majalengka, 2025)
This study explores the role of football as a medium for character formation based on the “7 Habits of Great Indonesian Children” in one of the elementary schools in Labuhan Ratu District. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation involving teachers and students. The findings show that football activities effectively internalize key character values such as discipline, teamwork, responsibility, respect, and problem-solving. Through structured training and game-based learning, students naturally practice positive habits that support their personal and social development. The study concludes that football can serve as a strategic vehicle for character education when integrated with targeted value-based frameworks.